Light Absorption in Coralline Algae (Rhodophyta): A Morphological and Functional Approach to Understanding Species Distribution in a Coral Reef Lagoon - Vásquez-Elizondo, Román M.; Enríquez, Susana (Frontiers in Marine Science, 2017)
Red coralline algae are a cosmopolitan group with the ability to precipitate CaCO3 within the walls of their vegetative cells. The resultant carbonate structure is key for explaining their ecological success, as it provides protection against herbivores and resistance to water motion. However, its potential contribution to enhance thallus light absorption efficiency through multiple light scattering on algal skeleton, similar to the effect documented for scleractinian corals, has not been yet investigated. Here, we initiate this analysis, characterizing thallus optical properties of three coralline species, which differed in pigment content and thallus mass area (TMA, gDW m-2). The three species, the rhodolith Neogoniolithon sp., the crustose coralline alga (CCA), Lithothamnion sp., and the articulated alga Amphiroa tribulus, represent the more distinctive coralline growth-forms and were able to colonize contrasting light environments in Caribbean coral reefs. The thicker thalli of the rhodoliths were the most efficient light collectors, as evidenced by their higher pigment absorption efficiency (a*Chla; m2 mgChla-1) and photosynthetic rates per unit area. This could explain rhodolith success in oligotrophic, highly illuminated reef environments. In contrast, the thinner thalli of the CCA, a low-light specialist, showed the highest metabolic rates normalized to mass and the highest light absorption efficiencies per unit mass (a*M; m2 gdw-1). Therefore, the ecological success of the CCA in cryptic habitats within the reef cannot be explained only by its low-light physiology, but also by its capacity to reduce the structural costs of their thalli, and thus of its new growth. Lastly, the ecological success of Amphiroa tribulus, which displayed intermediate values for the efficiency of light absorption, metabolic rates and TMA, was explained by its ability to construct the largest light collectors (algal canopies) thanks to the presence of flexible, non-calcified segments (genicula). This ability enables enhanced photosynthetic and carbonate production at the organism/canopy level. The resulting fragile canopy survives best within the protection provided by colonies of the lettuce coral Agaricia agaricites. In conclusion, our study demonstrates the utility of optical traits as powerful tools to investigate differences in the competitive abilities, abundances and niche distribution among algal species and/or growth-forms.